Correlation of Behavioral Attributes of Post Graduate Residents with the Compliance of Patients Undergoing Orthodontic Treatment - Imtiaz, Annam; Qamar, Rehan; Majid, Mian Aneeq; Nasir, Kinza; Nayab, Tayyaba (Pakistan Armed Forces Medical Journal, 2025)
Objective: To correlate patients perceived behavioral attributes of postgraduate residents to the assessed compliance status of the patients undergoing orthodontic treatment. Study Design: Analytical cross-sectional. Place and Duration of the Study: Department of Orthodontics, University College of Dentistry, The University of Lahore, Nov 2022 to Feb 2023. Methodology: The study comprised 215 orthodontic patients, who completed the pre-validated standardized proformas about the behavioral attributes of their treating postgraduate residents, comprising 25 questions based on 5-point Likert scale. The respective postgraduate residents assessed the patients’ compliance based on the Orthodontic Patient Cooperation Scale (OPCS) where postgraduate residents and their patients were blind to each other’s responses. The age range of the patients was 12-29 years with mean age being 18.84±4.03 years. Non-probability convenience sampling technique was used. Results: A moderate positive correlation was noted between the behavior of the resident explaining the procedure step by step (Item 17) and the average patients’ compliance score (r=0.47, p<0.001). A mild positive correlation was present for the behavior of postgraduate residents, warning the patient if the procedure hurts (Item 1, r=0.28, p<0.001), being polite (Item 9, r=0.24, p<0.001) and punctual (Item 25, r=0.19, p=0.01) with favorable compliance of patients. Conclusion: Behavioral attributes of postgraduate residents positively correlate with the compliance of patients undergoing orthodontic treatment. Clinicians’ behavior and step-by-step explanations, counseling of the patients for painful procedures, politeness in conversation and punctuality may lead to improved patient compliance score.